Gender-specific effects of cytokine gene polymorphisms on childhood vaccine responses - Baynam, G.; Zhang, Guicheng; Khoo, S.; Sly, P.; Holt, P.; Goldblatt, J.; Le Souëf, P. (Elsevier, 2008)
Cytokine gene polymorphisms affect vaccine responses and gender-specific effects are known for many phenotypes. Therefore, this study investigated gender-specific effects of cytokine gene polymorphisms on vaccine responses. In 263 2-year-old subjects selected for parental history of atopy, boys with IL-4 C-589T and IL-4Ra I50V genotypes associated with atopy had increased Diptheria Toxoid (DiphTox) and Tetanus Toxoid (TetTox) responses compared with the remaining alleles (IL-4 C-589T: DipTox p = 0.01, TetTox p = 0.04; IL-4Ra.I50V: DipTox p = 0.04, TetTox p = 0.08). Contrastingly, girls with IL-10 -592C genotypes associated with atopy had lower levels of DiphTox (p = 0.03) and TetTox (p = 0.02) responses compared with the remaining allele. Additionally, interaction effects were found for IL-4 C-589T (p = 0.01) and IL-4Ra I50V (p = 0.04) polymorphisms. In conclusion, these findings support the interaction of primary genetic and modifying factors on vaccine responses and the importance of atopic genetics to these responses. © 2008 Elsevier Ltd. All rights reserved.